3D object recognition considering light conditions - Picos, Kenia (My University, 2019)
There is a demand to solve object recognition under complex conditions such as noise, geometric distortions and changes of visualization caused by an incident light source. Recognition systems must process a lot amount of data, and make decisions in real time to accomplish their tasks.
Keywords: Sistema de reconocimientos; GPU filtros; Campus Tijuana